RESEARCH ON THE EFFECTIVENESS OF TEACHING BIOSTATISTICS OF FUTURE PHYSICIANS - Gruzieva, Tetiana S; Stuchynska, Nataliia V; Inshakova, Hanna V (Wiadomości lekarskie (1960), 2020)
The aim: To evaluate the effectiveness of teaching biostatistics of future physicians in the context of the introduction of a new curriculum on the subject «Social Medicine, Public Health» in the «Biostatistics» module. Materials and methods: During the study 2 groups of students that had different curriculum were formed - experimental group (EG) (n = 257) and control group (CG) (n = 272). Their level of knowledge, skills and abilities was determined with the help of a sociological survey. The level of acquired competencies of students was assessed according to the developed motivational, cognitive, activity and reflective criteria. Bibliosemantic, analytical, sociological, medical-statistical and experimental methods were used to analyze the results. Results: The study analyzed and identified differences in a number of indicators related to the combination of work and study (EG - 28.4±2.8, CG - 43.3±3.0 per 100 students), preferences for the study of biostatistics (EG) - 47.2±3.1, CG - 30.5±2.8 per 100), acquaintances with statistical sizes and methods before the beginning of training of biostatistics (EG - 32.9±3.0, CG - 41.1±3.0 per 100), the presence of difficulties in mastering the subject (EG - 50.2±3.1, CG - 53.2±3.0 per 100). The reasons for dissatisfaction with the educational process, the optimal forms and methods of teaching biostatistics were identified. The proposals of students to improve the quality of teaching the subject are studied. The plans of the participants of the experiment for further study of biostatistics and its use in future professional activities have been clarified. Conclusions: The data obtained indicate that the implementation of the new curriculum «Social Medicine, Public Health» in the module «Biostatistics» has had a positive impact on improving the professional competence of students in biostatistics, which proves its effectiveness.